2017
DOI: 10.1080/14647273.2017.1334130
|View full text |Cite
|
Sign up to set email alerts
|

Thicker endometrial linings are associated with better IVF outcomes: a cohort of 6331 women

Abstract: Our objective was to determine if a correlation exists between endometrial thickness measured on the day of ovulation trigger during an in vitro fertilization (IVF) cycle and pregnancy outcomes among non-cancelled cycles. We performed a retrospective cohort study looking at 6331 women undergoing their first, fresh autologous IVF cycle from 1 May 2004 to 31 December 2012 at Boston IVF (Waltham, MA). Our primary outcome was the risk ratio (RR) of live birth and positive β-hCG. We found that thicker endometrial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
5
17
0
1
Order By: Relevance
“…Previous studies have shown that increased endometrial thickness can significantly improve pregnancy outcomes among women undergoing IVF‐ET . Consistent with those studies, a significantly higher pregnancy rate, implantation rate, and live delivery rate were observed for women whose endometrium was thicker than 7 mm as compared with those whose endometrium was thinner than 7 mm in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies have shown that increased endometrial thickness can significantly improve pregnancy outcomes among women undergoing IVF‐ET . Consistent with those studies, a significantly higher pregnancy rate, implantation rate, and live delivery rate were observed for women whose endometrium was thicker than 7 mm as compared with those whose endometrium was thinner than 7 mm in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that increased endometrial thickness can significantly improve pregnancy outcomes among women undergoing IVF-ET. 12,14 Consistent with those studies, a significantly higher pregnancy rate, implantation rate, and live delivery rate were observed for women whose endometrium was thicker than 7 mm as compared with those whose endometrium was thinner than 7 mm in the present study. In addition, the lowest rates of spontaneous abortion were observed for women with an endometrial thickness between 7 and 12 mm, whereas an endometrium thicker than 12 mm showed higher abortion rates.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The fact that better endometrial thickness could help achieve higher pregnancy rates is understandable and has been made known [11], the hypothesis that vaginal sildenafil could directly increase clinical pregnancy rates, although previously studied has not been well established.…”
Section: Discussionmentioning
confidence: 99%